Análise e modelagem integrada da qualidade da água em um sistema urbano canal-reservatório eutrofizado, localizado em Fortaleza/Ce. - Araújo, Germário Marcos (2016)
This paper presents an integrated analysis of water quality in a system comprising a drainage channel and the reservoir Santo Anastácio - ASA, located in Fortaleza-CE. For this monitoring were performed campaigns that aimed to characterize spatially and seasonally, the flow parameters, pH, temperature, DO, BOD, COD, PT, NT and Cl_a. It was observed even during periods dried, a significant increase in flow along the channel, by virtue of connections illegal sewage. There was also a constant release of waste solids in the channel. Consequently these fillers, it can be seen deterioration significant quality along the channel, then a recovery ASA in which He acted similarly to a stabilization pond. However, the recovery It was not enough that the water quality returned to its original condition, or is, at the channel entrance. Then we calculated the Trophic State Index - EIT for ASA, and 100% of the monitoring period the vessel was rated as hypereutrophic (IET> 63), which is the maximum rating for the level of eutrophication. Comparing the results obtained with ASA to previous work, was observed over 15 years, a progressive degradation of water quality, the full and Cl_a match parameters highlighting that were much higher than advocates CONAMA Resolution 357/05 for water bodies class 2. It point out that all the polluting load out ASA proceeds to Maranguapinho river, one of the main drainage courses in the metropolitan region of Fortaleza and currently undergoing revitalization process, but only on the margins of the main course. This indicates the need to carry out integrated actions in terms concerning the recovery of water quality in urban basins. Aiming to get a tool to evaluate different water quality scenarios in the integrated system channel-ASA, has developed a mathematical model for the match. The model for the Drainage channel is obtained by considering the advection processes and reaction steady over the passages, including terms relating to the side entrance sewage through illegal connections and phosphorus present in the waste load. The model used for the reservoir considered the input and output loads, thereby such as accumulation of reaction processes and on the basis of complete mixing model. Through adjustment of the model to the data field, reaction rates were obtained to the channel (kcanal) and ASA (kreservatório) with values ​​varying over the period monitoring, including presenting negative values ​​indicate the presence internal loads in these extremely polluted environments, probably due the resuspension processes and release of phosphorus deposited in the channel bottom and the weir. However, the overall balance, average values ​​for the coefficients the reaction channel (kcanal of 4.32 day -1) and ASA (kreservatório = 22.84 years-1) were significantly higher than those obtained in the literature for temperate regions or tropical. This may be related to increased water temperature, which in turn results in a higher phosphorus intake by phytoplankton and greater this nutrient settling velocity due to lower viscosity of water. Possession of the calibrated model were made twelve simulations of scenarios proposals for improvements to the canal and the ASA. It was only possible to meet release pattern of CONAMA Resolution 357/05 when decreased phosphorus concentration of shares were combined tributary to the channel and total removal of phosphorus loads related to wastewater / solid waste. It is expected that This research will assist in the management of urban basins, especially in semi-arid regions of Brazil.